2015
DOI: 10.1103/physreva.91.023802
|View full text |Cite
|
Sign up to set email alerts
|

Pulse propagation, population transfer, and light storage in five-level media

Abstract: We consider adiabatic interaction of five-level atomic systems and their media with four short laser pulses under the condition of all two-photon detunings being zero. We derive analytical expressions for eigenvalues of the system's Hamiltonian and determine conditions of adiabaticity for both the atom and the medium. We analyze, in detail, the system's behavior when the eigenvalue with nonvanishing energy is realized. As distinct from the usual dark state of a five-level system (corresponding to zero eigenval… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Our formulation can be generalized for a weak longitudinal grating, by adopting the approach in [60][61][62][63]. The formulation will also be trivially valid for pulse propagation in (uniform) atomic media [2,3,30,31] and quantum models of stopped light [26][27][28], which as noted, were so far usually modelled with rather simplistic models in which second-order and higher-order dispersion effects were neglected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our formulation can be generalized for a weak longitudinal grating, by adopting the approach in [60][61][62][63]. The formulation will also be trivially valid for pulse propagation in (uniform) atomic media [2,3,30,31] and quantum models of stopped light [26][27][28], which as noted, were so far usually modelled with rather simplistic models in which second-order and higher-order dispersion effects were neglected.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, slow light was demonstrated also at optical frequencies [2][3][4][5][6][7], and it was even shown that the light can nearly be brought to a standstill ("stopped light") [8][9][10]. As a result, various potential applications emerged, including in particular optical memory in optical communication systems [6,[11][12][13], nonlinear optics [7,[14][15][16][17][18][19][20][21], Brillouin scattering [22,23], and more recently, quantum computing [10,[24][25][26][27][28][29], e.g., based on electromagnetic induced transparency [2,3,8,9,[30][31][32]; Additional potential applications are tissue imaging [33], sensing [34], low threshold lasing [35][36][37][38][39], photochemistry [40,41] and even table...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar five-level system has been studied in Refs. [24] and [25], although under different conditions. State 4 decays to states 1 and 2 at rates !…”
Section: Five-level Geit Systemmentioning
confidence: 97%
“…A similar five-level system has been studied in Refs. [24] and [25] To see the behavior of the system at the center of the dip more transparently, it is instructive to consider a reduced system produced via adiabatic elimination of states 4 and 5 (this approximation is for illustration only, and will not be made in the ME analysis as well as the semiclassical analysis to follow in this section). The system is then reduced to a configuration similar to the Λ-type EIT system as shown in Fig.…”
Section: Five-level Geit Systemmentioning
confidence: 99%